PREVALENCE AND RISK FACTORS OF GASTROESOPHAGEAL REFLUX DISEASE (GERD) IN MEDICAL COLLEGE STUDENTS - IQBAL , N; KHAN , A; YOUSAF , MS; KHAN , MA; ALAM , I; REHMAN , RU; AHMAD , Y; KHAN , MA (Biological and Clinical Sciences Research Journal, 2024)
Gastro-esophageal reflux disease (GERD) is a common gastrointestinal disorder characterized by the reflux of stomach contents into the esophagus, leading to heartburn, regurgitation, and chest pain. Objectives: The study’s main aim is to find the prevalence and risk factors of gastroesophageal reflux disease in medical college students. Methods: This cross-sectional study was conducted at Allama Iqbal Medical College Lahore from October 2023 to March 2024. Data were collected from 550 medical college students from 1st year, 2nd, 3rd, 4th and 5th year. Data were collected through an online survey, including demographic data, GERD symptoms, dietary habits and lifestyle factors, and stress levels. GERD symptoms were reported, which include all data related to heartburn, chest pain and dysphagia. Results: Data were collected from 550 participants. The mean age of the participants (with GERD) was 24.0 ± 3.0 years, and without GERD, 23.0 ± 2.5 years. There were 65% female and 35 % male in the GERD group and 55% female and 45% male in the without GERD group. Students with GERD exhibited significantly higher prevalence rates of certain lifestyle factors compared to those without GERD. Specifically, students with GERD reported higher rates of consumption of spicy/acidic foods (50% vs. 35%), high intake of caffeine/carbonated beverages (60% vs. 40%), irregular meal patterns (40% vs. 20%), large meals before bedtime (30% vs. 15%), and sedentary lifestyle behaviors (70% vs. 40%). These differences were statistically significant, as indicated by the p-values <0.05 for consumption of spicy/acidic foods and large meals before bedtime, <0.01 for high intake of caffeine/carbonated beverages and irregular meal patterns, and <0.001 for sedentary lifestyle behaviours. Conclusion: It is concluded that gastroesophageal reflux disease (GERD) presents a significant health concern among medical college students, with a notable prevalence of symptoms reported in this population.